Surgical approach to single-level symptomatic thoracic disc herniations through costotransversectomy: A report of ten case series - Dalila Scoscina; Silvia Amico; Edoardo Angeletti; Monia Martiniani; Leonard Meco; Nicola Specchia; Antonio Pompilio Gigante (Journal of Craniovertebral Junction and Spine, 2023)
Study Design: This was an observational study. Objectives: The treatment of symptomatic thoracic disc herniation (TDH) remains a matter of debate. We report our experience with ten patients affected by symptomatic TDH, surgically treated through costotransversectomy. Methods: A total of ten patients (four men and six women) with single-level symptomatic TDH were surgically treated by two senior spine surgeons at our institution between 2009 and 2021. The most common type was a soft hernia. TDHs were classified as lateral (5) or paracentral (5). Preoperative clinical symptoms were varied. The diagnosis was confirmed by computed tomography (CT) and magnetic resonance imaging of the thoracic spine. The mean follow-up period was 38 months (range: 12–67 months). The Oswestry Disability Index (ODI), the Frankel grading system, and the modified Japanese Orthopedic Association (mJOA) scoring system were used as outcome scores. Results: Postoperative CT study documented satisfactory decompression either on the nerve root or the spinal cord. All patients experienced a reduction of disability with an improved mean ODI score by 60%. Six patients reported total recovery of neurological function (Frankel Grade E) and four patients improved by 1 Grade (40%). The overall recovery rate estimated with the mJOA score was 43.5%. We reported the absence of significant difference in outcome compared to either calcified and noncalcified discs or paramedian and lateral location. Four patients had minor complications. No revision surgery was required. Conclusion: Costotransversectomy represents a valuable tool for spine surgeons. The major limit of this technique is the possibility to approach the anterior spinal cord.